Results on abstract integro hybrid evolution system with impulses on time scales. (February 2021) - Kumar, Vipin; Malik, Muslim; Djemai, Mohamed
Abstract: Our purpose in this manuscript is to study the existence of solution, stability analysis and exact controllability results for an abstract integro hybrid evolution system with impulses on time scales. Non-linear functional analysis, evolution operator theory and Banach contraction theorem have been used to establish these results. In the end, we present some theoretical and numerical examples for different time scales to illustrate the application of these analytical results.